Using 3D motion capture to analyze ice-hockey shooting technique on ice - Swaren, M.; Soehnlein, Q.; Holmberg, M.; Stöggl, T.; Björklund, G. (20th Annual Congress of the European College of Sport Science (ECSS), 24th-27th June 2015, Malmö -Sweden. Book of Abstracts, 2015)
Numerous studies have investigated shooting and skating technique in ice hockey. Studies performed on ice (Goktepe et al. 2010, Sci Res Essays) mostly have used high speed cameras to capture kinematic data while studies using 3D motion capture systems have been executed off ice by simulating real ice condition by using e.g. synthetic ice (Worobets et al. 2006, Sport Eng, Michaud-Paquette et al. 2011, Sport Biomech). Upjohn et al. (2008, Sport Biomech) stated that passive marker systems for motion capture have limited applications for collecting data in a field setting. Hence, the aims of the current study are to use a passive marker motion capture system to collect data of professional ice hockey players on ice in order to compare shooting techniques. Method: Two professional ice hockey players from EHC Red Bull Mu ich, in the top division in Germany, were recruited for the study. Both players used their own skates, gloves, helmets and sticks and wore tight fitting compression clothes. 56 reflective markers were placed on each player, including the stick, to facilitate full body analysis. Markers were also placed on the pucks for velocity measurements. Each player performed 10 slap shots and 10 on-timers, where the puck is hit directly from a pass and often used in power play. Data was collected by 20 Qualisys Uqus 7+ cameras (Qualisys AB, Gothenburg, Sweden) at 240 Hz, within a volume of 60x15x2 m. Results: Mean puck velocity for slap shots was 36.9 ± 1.0 m/s for player one and 36.0 ± 0.9 for player two. Larger differences were observed for the one-timers where player one had an average puck velocity of 39.3 ± 2.5 m/s versus 35.4 ± 1.0 for player two. The total mean puck velocity was higher for one-timers compared to slap shots (37.3 ± 2.8 vs. 36.4 ± 1.0 m/s).. Although one-timers had both a higher peak and mean puck acceleration than the slap shoots it was at the same time performed with a much less repeatability indicated by a larger CV for both players (34 and 14 % vs. 7 and 9 %) Discussion: In contrast to previous studies full body 3D data were successfully acquired from ice hockey players on ice by using passive markers and 20 infrared cameras. The system performed well for on ice measurements but the setup time of approximately 15 h should be taken in consideration for future studies. The collected data enables numerous possibilities to investigate different movements where puck velocity only is the first basic analysis performed with the data from the current study. Motion capture technology enables accurate 3D kinematic analysis and in the present study there were clear differences between highly skilled subjects in regard to performance and technique.